PENINGKATAN KEPUASAN PENUMPANG BUS RAPID TRANSIT (BRT) SEMARANG - Fadlilah Utami; Alifah Ratnawati (Jurnal Ekonomi dan Bisnis, 2016)
This study aim stodetermine the effect ofservice quality dimensions as seen from five dimensionsofphysical evidence/tangible, durability/reliability, responsiveness, assurance, and empathytowards Bus Rapid Transit passengers. Inthis study, data were collectedby using question naireto 96 respondents, which aims to determine the response of the respondents toeachvariable.The analysis which is used,includevalidity test, reliability test,classic assumptions test(multicollinearity, normality, heteroscedasticity), multiple linear regression analysis, goodnessof fittest (F test, ttest, the coefficientof determination). From the result that using the regressionanalysis showed that the variables of physical evidence / tangible, durability / reliability,responsiveness,assurance, and empathy, all have positive and significant of BRT passengerssatisfaction. With the influence of 56.3% while43.7%are influenced by other variables.Keywords:service quality,customersatisfaction, mass transportation